Secure Trust Node Acquisition and Access Control for Privacy-Preserving Expertise Trust in WBAN Networks - Al Barazanchi I.I.; Hashim W.; Thabit R.; Sekhar R.; Shah P.; Penubadi H.R. (Springer Science and Business Media Deutschland GmbH, 2025)
Wireless Body Area Network (WBAN) usage in healthcare has increased, making network reliability a critical issue. In a WBAN network, this study addresses safe and accurate access to trustworthy nodes while maintaining user privacy. Three key goals are to design a safe and accurate technique for accessing authentication networks and construct skill authentication networks. Examine their influence on users? medical information and provide user-type-based security. Control Modules for WBAN networks. This study proposes a unique trust node security and privacy method to achieve these goals. Using modern cryptographic protocols and privacy protection approaches, the proposed solution improves trusted node acquisition accuracy and user privacy. In addition, the article examines knowledge trust networks and their influence on medical data. It evaluates and validates trustworthy nodes? processing of sensitive medical information to protect user data. The suggested technique uses user-characteristic-based secure access management to access WBAN networks. This module restricts network access to approved users with certain characteristics, boosting security and preventing unauthorized access. This study allows the suggested strategy to be implemented in a simulated WBAN setting, going beyond theoretical frameworks. The results demonstrate how a method for obtaining a secure trust node, establishing competent trust nodes, and implementing robust access control mechanisms emphasizes the importance of balancing accuracy and user privacy cultivation and advances safer healthcare systems in an era of interconnected medical devices. ? The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.